Dual entropic and enthalpic processes in the lower critical solution temperature phase separation of poly(vinyl methyl ether) aqueous solutions. Issue 6 (24th January 2019) - Song, Li; Lin, Jiaxiang; He, Yang; Li, Jingqing; Sheng, Jing; Jiang, Shichun; Huang, Dinghai
ABSTRACT: In the lower critical solution temperature phase separation of poly(vinyl methyl ether) aqueous solutions, the process corresponding to the weakening of the hydrogen bond interaction with increasing temperature is dominant and occurs over the entire concentration region of solutions and over a broad temperature range from 30 to 41°C, giving rise to the energetic enthalpic effect during phase separation, while the conformational change, that is, collapse of the swollen polymer coils, occurs only in the swelling polymer solution when the water concentration is above 38.3 wt %, giving rise to the entropic effect during phase separation. In addition, the entropic process corresponding to the collapse of the polymer coils occurs in a much narrow theta temperature range from 35.5 to 37°C. If the solution is held at a constant temperature for a sufficiently long time, 90% collapse of the polymer coils occurs in only the 0.5 °C temperature region between 35.5 and 36°C. Accordingly, in the enthalpic process, the most dramatic blueshift of the ν C‐O bond peak occurs in the temperature range between 35 and 41°C, while this blueshift is only approximately 2 cm −1 in the temperature range from 30 to 35°C, prior to the collapse of the polymer coils due to the entropic effect. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 323–330 Abstract : In temperature‐induced lower critical solution temperature phase separation, the process corresponding to the weakening of the hydrogen bond interaction with increasing temperature is dominant and occurs over the entire concentration region of the solutions and over a broad temperature range, giving rise to the energetic enthalpic effect in the phase separation. By contrast, the conformational change, that is, the collapse of the swollen polymer coils, occurs only in the swelling polymer solution when the water concentration is above 38.3 wt % and in a much narrower theta temperature range from 35.5 to 37°C, giving rise to the entropic effect during phase separation.